Pendidikan Bahasa sebagai Upaya Membangun Generasi Unggul di Era Digital - Rumodar, Gresye Karunia; Messakh, Jefrit Johanis; Naibaho, Lamhot (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2024)
Language education in the context of the digital era is a strategic effort to build a superior generation. In this era, language skills are no longer only related to verbal communication, but also include digital literacy and understanding bold content. language education in developing effective, critical and creative communication skills amidst the abundant flow of digital information. One of the main challenges in the digital era is how to integrate the use of technology in language learning without eliminating traditional values. Through an inclusive and innovative approach, language education is an alternative to help the younger generation to become independent thinkers, able to explore and interpret various sources of information wisely, and participate actively in a digitally connected global society. The aim of this research was to described language education as an effort to build a superior generation in the digital era. The method used in this research is literature study. The results of this research show that language education has an important role in forming a superior generation in the digital era. Through language education, individuals can develop communication skills, content understanding, and literacy skills that are much needed in an ever-evolving digital environment. With a strong understanding of language, future generations can utilize technology wisely, generate and analyze information critically, and participate actively in a variety of global contexts.